Primary Lymphoma Presenting in an Ascending Aortic Aneurysm: A Case Report - Schurman, Alexander M.; Mendoza, David; Rokkas, Chris K. (AORTA, 2020)
Small lymphocytic lymphoma (SLL) is rarely associated with thoracic aortic aneurysms. Aneurysm of the ascending aorta associated with SLL has never been reported before. We describe the case of an asymptomatic 68-year-old woman who presented with a 5.5-cm aneurysm of the ascending aorta and no prior history of hematological disorders. Following excision and repair, the surgical specimen showed infiltration of the aortic wall by lymphocytes, expressing markers consistent with SLL. While symptomatic SLL carries a poor prognosis, risk stratification tools are applied to guide management strategies in asymptomatic patients.
Keywords: aneurysm; aorta; lymphoma